Certification Corner A Monthly Quiz Answers and References. Issue 6 (1st June 2016) - Unknown
Abstract : Certification Corner lets Opflow readers sharpen their skills with a quick quiz of terminology, regulations, practices, and formulas pertinent to water/wastewater distribution system and treatment plant operations.